2008
DOI: 10.1097/shk.0b013e3181818617
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Depression in Sepsis

Abstract: Since the ancient Greeks, we have learned that the pathophysiology of the human diseases relies on blood-borne humoral factors. This was the case with the sepsis myocardial depression, whose associated morbidity and mortality remained untouched during the last decades. Despite the growing knowledge of the possible involved mechanisms, our understanding of this serious condition is still in its infancy. Controversies have surrounded the real origin of septic-induced myocardial dysfunction, and it has been ascri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 34 publications
2
42
0
11
Order By: Relevance
“…Data from different cohorts of patients with severe sepsis have identified multiple-organ failure, refractory shock, and respiratory failure as the main causes of death (20). Acute myocardial infarction and ventricular arrhythmias also contribute to mortality in severe sepsis; thus, myocardial dysfunction is a major contributor to mortality in critically ill patients with infections as also demonstrated by echocardiography (21)(22)(23). Pertinent to this, there is evidence that myocardial dysfunction in severe sepsis may be at least partly preventable, including experimental and retrospective studies that have found positive effects on mortality by β-blockers and statins (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Data from different cohorts of patients with severe sepsis have identified multiple-organ failure, refractory shock, and respiratory failure as the main causes of death (20). Acute myocardial infarction and ventricular arrhythmias also contribute to mortality in severe sepsis; thus, myocardial dysfunction is a major contributor to mortality in critically ill patients with infections as also demonstrated by echocardiography (21)(22)(23). Pertinent to this, there is evidence that myocardial dysfunction in severe sepsis may be at least partly preventable, including experimental and retrospective studies that have found positive effects on mortality by β-blockers and statins (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of sepsis-induced cardiac dysfunction have been reviewed extensively [35,[53][54][55][56][57][58][59]. Early sepsis is characterized by high levels of circulating catecholamines [20,60,61] that derive from the autonomous nervous system, the gut [62], lymphocytes [63,64] macrophages [65] and neutrophils [66,67].…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…In 10% to 20% of these patients with refractory hypotension, there is a clinical picture of low cardiac output due to severe myocardial dysfunction. [16]…”
Section: Discussionmentioning
confidence: 99%